BIOAKTIVITAS EKSTRAK METANOL DAUN NAMNAM SERTA KOMBINASINYA DENGAN MADU TRIGONA - La Ode Sumarlin; Agik Suprayogi; Min Rahminiwati; Achmad Tjahja; Dede Sukandar (Jurnal Teknologi dan Industri Pangan, 2015)
Namnam (Cynometra cauliflora L) and trigona honey are two natural ingredients that are potential to be developed in Indonesia. However, scientific evidence of its active compounds and bioactivity is still rarely found, particularly the combination of these two materials. Therefore, this research is to explore their active ingredients of combination of these two materials such as total phenolic, flavonoids, vitamin C and β-carotene and bioactive capabilities such as antioxidant activity and antibacterial activity. The analysis showed that antibacterial activity of methanol extract of Namnam leaves (EMDN) and trigona honey either in their sole form or combined form has antioxidant and antibacterial activity. The EMDN was more sensitive to Staphylococcus aureus (23.7±3.3 mm) than to Escherichia coli, while the Trigona honey (MT) more sensitive to Escherichia coli (32.6±4.4 mm) than Staphylococcus aureus (16.6±4.1 mm). Similarly, the combination of EMDN and MT was more sensitive to Escherichia coli (23±1.9 mm) than Staphylococcus aureus (17.6±2.6 mm). Analysis of the antioxidant activity also showed that EMDN provided the highest activity (IC50 0.0048±0.000 mg/mL), a combination EMDN and MT (IC50 0.0085±0.000 mg/mL) and MT (IC50 3.736±0.112 mg/mL). Moreover, this analysis also showed thatsole samples of MT and EMDN have total phenolic content, flavonoids, and vitamin C that were higher than the combination of MT and EMDN. However, the content of β-carotene in the combined form of MT and EMDN was higher. Thus trigona honey, methanol extract of leaves Namnam (Cynometra cauliflora L) in a single form or in a combination are potential to be utilized and developed as a source of antioxidants and antibacterial in the form of functional food.